APPLICATION OF ECLECTIC STYLE IN THE INTERIOR DESIGN OF ZOZO GARDEN CAFE, BANDAR LAMPUNG - Satria, Widi Dwi; Ujung, Verarisa Anastasia; Setyorini, Yurim Hatamaiya; Frisky, Hendra; Khairunnisa, Adenita Kamilia; Alamsyah, M Renaldi Ramadhan (Jurnal Ilmiah Arsitektur, 2024)
The growing popularity of cafes in Bandar Lampung is driven by the interest of young people who enjoy spending time in these venues. The lifestyle in Bandar Lampung has turned cafes into more than just dining spaces; they have become social and co-working environments. Zozo Garden Cafe distinguishes itself through its eclectic interior design, setting it apart from other cafes. This study explores the decor of the cafe, focusing on space-forming, space-supporting, and space-filling elements. The research uses a qualitative descriptive method with an exploratory approach, observing and analyzing the cafe's interior through visual observation. The findings show that Zozo Garden Cafe successfully implements an interior style that balances sociability, ambiance, and intimacy. The dynamic combination of space-forming, supporting, and filling components creates an appealing design for those who appreciate aesthetic interiors. The cafe’s uniqueness is highlighted by varied wall ornaments, textured and patterned floors, vintage windows, mixed-material ceilings, and distinct color schemes in every corner.